POTENSI PANGAN FUNGSIONAL SUMBER VITAMIN C DAN ZINK: COOKIES DAUN KELOR DAN LABU KUNING - St. Masithah (Media Gizi Pangan, 2023)
One of the efforts that have been made to deal with the challenge of micronutrient deficiencies is to utilize local food. Several studies have shown that the use of wheat flour from local food in the manufacture of cookies can increase the nutritional value of the product, so a study was conducted regarding the addition of moringa leaf and pumpkin flour to cookies. Analyze the content of vitamin C and zinc in cookies with the addition of moringa leaf and pumpkin flour. This study used an experimental research design which was carried out in two stages. The first stage: the manufacture of flour and cookie formulation which was carried out at the Stikes Salewangang Maros Nutritional Food Administration Laboratory. In the second stage, nutrient analysis was carried out at the Makassar Health Laboratory Center (BBLK).The results of the analysis of the content of micronutrients with 3 repetitions showed that the zinc content was 120.77 mg/g while the vitamin C was 1275.22 mg/g. So, by consuming 3 pieces of cookies can meet the daily zinc needs of children aged 6-11 months and children aged 1-3 years. Meanwhile, for vitamin C, consuming 3 pieces of cookies can meet the needs of vitamin C for children aged 1-3 years and consuming 4 pieces of cookies can meet the daily needs of children aged 6-11 months.The addition of moringa leaf flour and pumpkin flour to the cookies of this study increased the micronutrient content of vitamin C and zinc compared to cookies in general, but the results of the analysis of the content of vitamin C